RIDOS: A new system for online computation of the delivered dose distributions in scanning ion beam therapy. (April 2019) - Giordanengo, S.; Vignati, A.; Attili, A.; Ciocca, M.; Donetti, M.; Fausti, F.; Manganaro, L.; Milian, F.M.; Molinelli, S.; Monaco, V.; Russo, G.; Sacchi, R.; et al.
Highlights: Online dose computation with scanned ion beams. Sub-second GPU-based ion dose calculation. Online monitoring of dose delivered accuracy. Forward dose calculation integrated in a dose delivery system for particle therapy. Abstract: Purpose: To describe a new system for scanned ion beam therapy, named RIDOS (Real-time Ion DOse planning and delivery System), which performs real time delivered dose verification integrating the information from a clinical beam monitoring system with a Graphic Processing Unit (GPU) based dose calculation in patient Computed Tomography. Methods: A benchmarked dose computation algorithm for scanned ion beams has been parallelized and adapted to run on a GPU architecture. A workstation equipped with a NVIDIA GPU has been interfaced through a National Instruments PXI-crate with the dose delivery system of the Italian National Center of Oncological Hadrontherapy (CNAO) to receive in real-time the measured beam parameters. Data from a patient monitoring system are also collected to associate the respiratory phases with each spot during the delivery of the dose. Using both measured and planned spot properties, RIDOS evaluates during the few seconds of inter-spill time the cumulative delivered and prescribed dose distributions and compares them through a fast γ-index algorithm. Results: The accuracy of the GPU-based algorithms was assessed against the CPU-based ones and the differences were found below 1‰. The cumulative planned and delivered doses are computed at the end of each spill in about 300 ms, while the dose comparison takes approximatively 400 ms. The whole operation provides the results before the next spill starts. Conclusions: RIDOS system is able to provide a fast computation of the delivered dose in the inter-spill time of the CNAO facility and allows to monitor online the dose deposition accuracy all along the treatment.